Faktor-Faktor Yang Mempengaruhi Kinerja Keuangan Pada Perusahaan Manufaktur - Arvielda, Thio Lie Sha (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2021)
This study aims to obtain empirical evidence of the effect of sales growth, firm debt, liquidity and firm size on financial performance. The sample used in this study is a manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2017-2019, and obtained as many as 82 data. This study uses purposive sampling and uses Eviews 12 in processing the data. The results showed that firm debt has a negative and significant effect on financial performance. While sales growth, liquidity and firm size has insignificant effect on financial performance, and has a positive and insignificant effect on financial performance The implication of this research is that a company requires high quality management so as to assist the company in improving its financial performance so that the company can compete and maintain its sustainability.